2014
DOI: 10.3391/bir.2014.3.2.05
|View full text |Cite
|
Sign up to set email alerts
|

First record of Naineris setosa (Verrill, 1900) (Annelida: Polychaeta: Orbiniidae) in the Western Mediterranean Sea

Abstract: The Asian kelp Undaria pinnatifida (Harvey) Suringar 1873 was found for the first time in Belfast Lough, Northern Ireland during 2012 and was probably established in 2013. This currently is the most northern locality in Europe. The recent expansion around Britain is likely to continue with further colonisation in Ireland and extension to Scotland. Conditions are suitable for colonisation of Celtic, North and perhaps Norwegian Sea coasts, where it is likely to become an important fouling organism on marinas, aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…setosa is associated with stressed habitat or is a tolerant opportunistic species. In the Mediterranean Sea it has been previously collected from heavily polluted habitats, such as black anoxic muds (Blake and Giangrande 2011) and in these environments it was able to withstand salinities as high as 43.1 PSU (Khedhri et al 2014). In Santa Gilla lagoon, in the station where highest densities were achieved, both temperature and salinity fluctuated dramatically on a seasonal pattern, with temperatures ranging from 23.9°C in September to 11.6°C in December and salinity ranging from 37 (PSU) in September to 3.8 (PSU) in March; in none of these extreme environmental conditions population densities were observed to decrease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…setosa is associated with stressed habitat or is a tolerant opportunistic species. In the Mediterranean Sea it has been previously collected from heavily polluted habitats, such as black anoxic muds (Blake and Giangrande 2011) and in these environments it was able to withstand salinities as high as 43.1 PSU (Khedhri et al 2014). In Santa Gilla lagoon, in the station where highest densities were achieved, both temperature and salinity fluctuated dramatically on a seasonal pattern, with temperatures ranging from 23.9°C in September to 11.6°C in December and salinity ranging from 37 (PSU) in September to 3.8 (PSU) in March; in none of these extreme environmental conditions population densities were observed to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…), but its presence in two successive years indicated that the population was established, even though numbers were clearly decreasing from the first to the second year (Khedhri et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although molluscs still remain the principal group despite their decrease, polychaetes such as Euclymene droebachiensis, Glycera tridactyle and Naineris setosa (newly recorded by Khedhri et al 2014) have greatly increased followed by crustaceans including the amphipod Echinogammarus sp. and the decapod Carcinus aestuarii.…”
Section: Macro-benthic Communitymentioning
confidence: 99%